EPISTEMOLOGI KEKUASAAN DALAM SISTEM POLITIK ISLAM - Mulia Harahap, Sumper (IAIN Padangsidimpuan, 2014)
Abstract: The Concept of Â the government has given a serious dialogue among Muslim thinkers and caused a variety of perceptions and not only in the theoretical, conceptual, but also entered the area of practical politics that they often bring discord and disunity among Muslims. In Islamic political thought, talking state and government by Islamic political theorists lead to two goals. First, to find the ideals of Islam on the country or establishing government (emphasizing the theoretical and formal aspects) is by trying answering the question